PENGGUNAAN BAHASA PADA ANAK BERKEBUTUHAN KHUSUS (DOWN SINDROM): KAJIAN PSIKOLINGUISTIK - Astary Nurdyna; Ahadi Sulissusiawan; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe language use, sound patterns, phonological deviations, and language barriers or disorders in children with special needs (Nurul Huda's case). The research method used is descriptive. This study uses primary data obtained directly from informants. Data collection techniques are observation, documentation, and interviews. Data collection tools used were recording devices, writing instruments, and notebooks. The results of the analysis show that the use of language in down syndrome children is very different. Down syndrome children are only able to say one word, because of the minimal vocabulary. When asking for something, Down syndrome children will point to the object they want. Down syndrome children have difficulty speaking vowels / a / and / i /, bilabial / p /, and vibrating sounds / r /. Children with Down syndrome also have difficulty pronouncing the correct articulations and even voices that are not clear, and sometimes make voices that are unclear without meaning that cannot be understood.Keywords: Down Syndrome , Language Use, Psycholinguistics